Bibliometric Analysis of Anatolia Turizm Araştırmaları Dergisi: An Analysis of Research Subjects and Institutional Collabration through Social Network Analysis - Deniz Karagöz; Nazmi Kozak (Türk Kütüphaneciliği)
Research subjects and collaboration between universities are important knowledge fields about forms of knowledge networks structures in a scientific community and flow of knowledge traffic. The aims of this study revealed to tourism knowledge network structure and institutional collaboration and examined to the roles of research subjects and collaboration into tourism network structure based on published articles in Anatolia Turizm Araştırmaları Dergisi. The data was collected from refereed articles in Anatolia Turizm Araştırmaları Dergisi between years of 1997-2010. Social Network Analysis is used to define network structure and to examine links between structures. For that purpose, UCINET and Netdraw programs were utilized. At the end of this study, tourism knowledge structure generally has central structure rather than interdisciplinary structure. Management, marketing, economy, education, accounting-finance, health and transportation research subjects are to be linked with each other rather than other research subjects. In this research, institutional collaborations are determined in low degree. In addition important roles are determined of University of Dokuz Eylül, University of Gazi and University of Mersin at institutional collaboration and separation of knowledge to other universities.